Effect of implementing business risk management in micro, small medium enterprise - Kelvin Kelvin; Nicholas Lim; Vincent Vincent; Welwen Welwen (Junal Ilmu Manajemen, 2023)
Risk management is very important to do because it can prepare the company to face certain conditions that cause losses for the company. The research method using qualitative, qualitative types that the author uses are interviews and observations. The author's goal of choosing MSME Blackforest Cakeshop as a partner in carrying out this project is because the authors consider that MSME Blackforest Cakeshop has a wide market reach and many consumers. In addition, the MSME Blackforest Cakeshop is located in one of the economic centers of the city of Batam which has very promising market opportunities and the author wants to advance MSME partners by providing advice on how high the risk of this writing partner is in the business world. This study aims to determine the application of risk. The contribution of the research is that it can provide risk management analysis for MSME businesses, especially Blackforest Cakeshop using a risk matrix so that the impact on MSME businesses can be known and solutions that can be applied to risk management problems in Blackforest Cakeshop MSMEs.